Clinical differences between men and women in a Swedish treatment-seeking population with gambling disorder - Miller, Louise; Mide, Mikael; Arvidson, Elin; Söderpalm Gordh, Anna (Frontiers in Psychiatry, 2023)
The purpose of this study was to explore clinical differences in Swedish treatment-seeking men and women with gambling disorder (GD). As the prevalence of GD is increasing among women, even though men are still highly overrepresented, the characteristic differences between men and women seeking treatment becomes increasingly important. A sample of 204 patients with GD (26.5% women and 73.5% men) at an outpatient clinic were diagnosed using the SCI-GD, screened for comorbid diagnoses using the MINI, and further completed a range of self-report questionnaires measuring demographics, GD, alcohol and other drug problems, symptoms of depression and anxiety, and pathways into gambling problems. Several characteristics differed between treatment-seeking men and women in our sample. Examples of differences between genders included age, onset age, living situation, duration, alcohol and drug problems, comorbidity and pathways leading into gambling problems. The most evident difference was that women, in addition to GD, showed more symptoms of anxiety and depression than men while men had a higher degree of substance use problems compared to women. Differences in clinical features between men and women are important to consider in treatment planning and possibly for future gender-based interventions.